2012
DOI: 10.1016/j.molcel.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Ser7 Phosphorylation of the CTD Recruits the RPAP2 Ser5 Phosphatase to snRNA Genes

Abstract: SummaryThe carboxy-terminal domain (CTD) of the large subunit of RNA polymerase II (Pol II) comprises multiple heptapeptide repeats of the consensus Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7. Reversible phosphorylation of Ser2, Ser5, and Ser7 during the transcription cycle mediates the sequential recruitment of transcription/RNA processing factors. Phosphorylation of Ser7 is required for recruitment of the gene type-specific Integrator complex to the Pol II-transcribed small nuclear (sn)RNA genes. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 39 publications
(91 reference statements)
12
155
1
Order By: Relevance
“…In this study, we show that S. cerevisiae Rtr1 is a regulator of Ser5 phosphorylation in the RNAPII CTD in agreement with previous findings (14,39,41,49,51,52). We show that deletion of RTR1 leads to global increases in Ser5-P CTD occupancy at RNAPII target genes, suggesting that Rtr1 is a general regulator of RNAPII phosphorylation during transcription elongation.…”
supporting
confidence: 92%
“…In this study, we show that S. cerevisiae Rtr1 is a regulator of Ser5 phosphorylation in the RNAPII CTD in agreement with previous findings (14,39,41,49,51,52). We show that deletion of RTR1 leads to global increases in Ser5-P CTD occupancy at RNAPII target genes, suggesting that Rtr1 is a general regulator of RNAPII phosphorylation during transcription elongation.…”
supporting
confidence: 92%
“…Depletion of any of these factors would be predicted to extinguish U7-GFP promoter activity and would not result in GFP expression. Interestingly, we also did not score the fly ortholog of RPAP2 (CG34183), which has been suggested to play an important role in mediating Integrator's association to the RNAPII CTD (Egloff et al 2012). Depleting fly RPAP2 did not give rise to snRNA misprocessing in our hands, suggesting that RPAP2 may fall into the group of factors we mentioned above or may not be critical in Drosophila.…”
Section: Discussionmentioning
confidence: 63%
“…Alternatively, stringent Ser5 dephosphorylation by phosphatases such as Rtr1 or Fcp1 in yeast 43,44 is required in order to render Ser2 phosphorylation possible. A recent study has indeed identified that the human RPAP2 phosphatase specifically recognizes Ser7 phosphorylation marks on the CTD to facilitate Ser5 dephosphorylation 45 . In a similar line of argument, a universal RNAPII CTD cycle along genes has been proposed, which is orchestrated by complex interplays between kinases, phosphatases and proline isomerases 46 .…”
Section: Y S P T S P S Y S P T S P S Y S P T S P Smentioning
confidence: 99%